Improving customer experience through accurate demand forecasting. (3rd December 2008) - Owusu, Gilbert; Shah, Mitul; Voudouris, Christos
Accurate demand forecasting is critical to improving customer experience. Accurately forecasting demand ensures that organisations have full visibility of customer requests. Such proactive visibility of demand in service organisations enables the right resources to be deployed at the right place and at the right time. We discuss the challenges faced in developing a demand forecasting system for service organisations. We also discuss the application of such a system at BT PLC, one of the leading communication service providers in the world.